STUDY ON THE EFFECTIVENESS OF INTRACISTERNAL ANTIBIOTIC TREATMENT FOR THE CONTROL OF MASTITIS IN GOATS - K. Hristov; R. Pepovich; B. Nikolov; G. Stoimenov (Trakia Journal of Sciences)
The aim of this study is to investigate the healing and prophylactic effect of drying-off antibiotic therapy using the selective and non-selective approach of administration of the antibiotics. First experimental group at the start of the dry period were treated non-selectively (all halves) intracisternally with antibiotics. In the second group, we only treated those halves that were diagnosed with subclinical mastitis. The control group of 9 goats was not treated. The number of somatic cells in treated groups after birth decreased from 2586 x 10³/ mL to 560 x 10³/mL in the first group and from 1978 x 10³/mL to 526 x 10³/mL in the second. Post partum, 10% of the halves were found to have subclinical mastitis. A healing effect was achieved in 25% (n=5) milk halves. New intramammary infections developed during the dry period also occurred in 5% (n=1) of the milk halves. In the second post-partum study, subclinical mastitis was observed only in 5% (n=1). Healing was achieved in 30% (n = 6) and the new intramammary infections (NIMIs) were 10% (n=2). In the control group, healing was only observed in 5% (n=1) and NIMI were 27.78% (n=5). The application of both treatment approaches, results in reduction in prevalence and manifestation of mastitis, as well as reduction of somatic cells in milk after kidding. The selective treatment method may be preferred, in order to reduce the cost of medications in conducting treatment and prophylaxis programs.